Optimasi pembuatan membran chitosam dalam penurunan COD dan BOD POME (Palm Oil Mill Effluent) [Optimization of the membrane production process to COD and BOD removal of POME (Palm Oil Mill Effluent)] - Sri WAHYUNI; . SISWANTO; Alia DAMAYANTI (E-Journal Menara Perkebunan, 2016)
Palm oil is one of the main commodities that cultivated in Indonesia as the biggest palm oil producer. One of the main problems in palm oil industry is the difficulty to degradate the palm oil mill effluent (POME) due to the high quantity and content of COD and BOD. In physico-chemical, POME can be processed using membrane filtration technology. Chitosan is one of the most widely used material forproducing membrane filtration. Composite of Chitosan-PVA-PEG is a highly mixture absorbent, which possibly can be used as a membrane in filtration process of POME. The experiment was started with the production of composite membrane, and then filtration application using cross-flow reactor system. The variables of this experiment were chitosan and PVA ratio (3:7, 4:5, 1:1, 6:4 and 7:3 (v/v)), and stirring speed (100 rpm and 300 rpm). The reactor test was conducted for 50 minutes and permeate were taken every 10 minutes. Filtration output parameters that were analyzed flux, COD and BOD. The result showed that the highest flux values in the variation of the stirring speed of 100 rpm and 300 rpm were 40.20 L/m2.hr and 27.15 L/m2.hr, respectively. The highest rejection values of COD and BOD were obtained in membrane ratio variation of 1:1 (v/v) and stirring speed of 300 rpm, which are 97.24% and 97.60%, respectitively.